2016
DOI: 10.1371/journal.pone.0154137
|View full text |Cite
|
Sign up to set email alerts
|

DNA Metabolism in Balance: Rapid Loss of a RecA-Based Hyperrec Phenotype

Abstract: The RecA recombinase of Escherichia coli has not evolved to optimally promote DNA pairing and strand exchange, the key processes of recombinational DNA repair. Instead, the recombinase function of RecA protein represents an evolutionary compromise between necessary levels of recombinational DNA repair and the potentially deleterious consequences of RecA functionality. A RecA variant, RecA D112R, promotes conjugational recombination at substantially enhanced levels. However, expression of the D112R RecA protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…In previous model, to assess this impact, the ssDNA binding properties of DprA protein were assayed using EMSA techniques. Previous studies suggested that a homodimer DprA is required for optimal binding to ssDNA, setting the lower limit of oligonucleotide length around 40-50 bases [6, 15, 27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous model, to assess this impact, the ssDNA binding properties of DprA protein were assayed using EMSA techniques. Previous studies suggested that a homodimer DprA is required for optimal binding to ssDNA, setting the lower limit of oligonucleotide length around 40-50 bases [6, 15, 27].…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings showed that some hyper-rec events observed for RecA mutants led to a decrease in the yield of recombinants. This suggests that the inhibitory effect of DprA on the yield of recombinants may correspond to its toxic effect on DNA intermediates [15].…”
Section: Dpra Significntly Inirecse the Frequeniy Of Reiombinctoncl E...mentioning
confidence: 99%
“…In fact, RecA did not evolve to have optimized activity but to preserve a balance between different cellular processes and genome stability. Indeed, uncontrolled recombination can interfere with DNA replication and transcription processes 5 . Moreover, bacterial chromosomes frequently carry multiple copies of genes at distinct chromosomal locations, for example, the 7 rrn operons in E. coli, and uncontrolled recombination can cause genetic damage through the aberrant elimination of genomic segments by recombination between repeated sequences 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Actually, recombinogenic over-activity can have deleterious effects on the cell: in fact, noncontrolled recombination can interfere with other biological processes, including DNA replication and transcription. Recombination can also cause genetic damage through the aberrant elimination of genomic segments by the recombination of repeat sequences (9). Hyper-recombinogenic recombinases can be used in vitro for diagnostic applications, particularly in the context of isothermal amplification.…”
Section: Introductionmentioning
confidence: 99%